Profitabilitas, Kepemilikan Manajerial, Kebijakan Dividen dan Nilai Perusahaan - Putra, Anak Agung Gede Alit Pramana; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2021)
The purpose of this study is to provide empirical evidence regarding the effect of financial and non-financial ratios on firm value. This research was conducted on a building construction sub-sector company on the Indonesia Stock Exchange (IDX). The number of samples taken was 32 observational samples, with non-probability sampling method, especially the sampling technique, namely purposive sampling. Data collection is done by non-participant observation. The analysis technique used is multiple linear regression analysis technique. The results of the analysis show that profitability, managerial ownership and dividend policy have a positive effect on the value of the building construction sub-sector companies on the Indonesia Stock Exchange in the 2016-2019. Keywords: Firm Value; Profitability; Managerial Ownership; Dividend.